A communicative model of premenstrual syndrome with social determinants of health: a path analysis. - Vakili, Fatemeh.; Nasiri, Malihe.; Jahanfar, Shayesteh.; Alamolhoda, Seideh Hanieh.; Hamzehgardeshi, Zeinab.; Salehi, Farank.; Fini, Masoome Hooshmand. (Tufts University. Tisch Library., 2025)
Keywords: Premenstrual syndrome, Path analysis, Structural determinants of health, Intermediate determinants of health.; Springer Open.